Aggressive CD4–CD8–CD45RA+CCR10– Primary Cutaneous Peripheral T-cell Lymphoma, Not Otherwise Specified: A Case Report - Natsumi Ikumi; Hideki Fujita; Tadashi Terui; Hiromichi Takahashi; Katsuhiro Miura; Yoshihiro Hatta; Masami Takei (Acta Dermato-Venereologica, 2019)

(untitled)
Abstract is missing (Short communication)